(untitled) (Clinics, 2013)
OBJECTIVES: This study tests the hypothesis that local or remote ischemic preconditioning may protect the intestinal mucosa against ischemia and reperfusion injuries resulting from temporary supraceliac aortic clamping. METHODS: Twenty-eight Wistar rats were divided into four groups: the sham surgery group, the supraceliac aortic occlusion group, the local ischemic preconditioning prior to supraceliac aortic occlusion group, and the remote ischemic preconditioning prior to supraceliac aortic occlusion group. Tissue samples from the small bowel were used for quantitative morphometric analysis of mucosal injury, and blood samples were collected for laboratory analyses. RESULTS: Supraceliac aortic occlusion decreased intestinal mucosal length by reducing villous height and elevated serum lactic dehydrogenase and lactate levels. Both local and remote ischemic preconditioning mitigated these histopathological and laboratory changes. CONCLUSIONS: Both local and remote ischemic preconditioning protect intestinal mucosa against ischemia and reperfusion injury following supraceliac aortic clamping.